2015
DOI: 10.1016/j.jmb.2015.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Basis of Common Human Disease: Insight into the Role of Missense SNPs from Genome-Wide Association Studies

Abstract: Recent genome wide association studies have led to the reliable identification of SNPs at a number of loci associated with increased risk of specific common human diseases. Each such locus implicates multiple possible candidate SNPs for involvement in disease mechanism. A variety of mechanisms may link the presence of a SNP to altered in vivo gene product function and hence contribute to disease risk. Here we report an analysis of the role of one of these mechanisms, missense SNPs (msSNPs) in proteins in seven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
45
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 85 publications
(137 reference statements)
2
45
0
Order By: Relevance
“…Of the human genomes sequenced by the 1000 Genomes Project (33), the GSDMB polymorphisms encoding the alleles containing either Gly299:Pro306 or Arg299:Ser306 are present at ∼50% frequency in the general population (22). The GSDMB SNPs associated with inflammatory disease risks encode the Arg299:Ser306 variant.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Of the human genomes sequenced by the 1000 Genomes Project (33), the GSDMB polymorphisms encoding the alleles containing either Gly299:Pro306 or Arg299:Ser306 are present at ∼50% frequency in the general population (22). The GSDMB SNPs associated with inflammatory disease risks encode the Arg299:Ser306 variant.…”
Section: Resultsmentioning
confidence: 99%
“…This study examined the "canonical" GSDMB isoform 1 [411 residues, Q8TAX9-1, identified in National Center for Biotechnology Information (NCBI) as GSDML and GSDMB isoform X3]. Analyses of GWAS data by Pal and Moult identified two GSDMB SNPs (dbSNP:rs2305479 and dbSNP:rs2305480) in linkage disequilibrium with a marker of disease risk (22). Based on the numbering scheme of the canonical GSDMB (Uniprot Q8TAX9-1), the rs230549 polymorphism corresponds to a Gly-to-Arg change at position 299, and the rs2305480 polymorphism corresponds to a Pro-to-Ser change at position 306 in the C-terminal domain of GSDMB (GSDMB_C).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…(8); for evidence of pleiotropy by Sivakumaran et al . (9); for loci associated with seven common diseases to identify possible causal missense variants by Pal and Moult, 2015 (10); and for identification of new targets for known drugs by Mullen et al . (11).…”
Section: Introductionmentioning
confidence: 99%